Virtual aid: a transformation of group mutual aid - Rodriguez-Keyes, Elizabeth; Cormier, Lisa (Journal of Baccalaureate Social Work, 2025)
Keywords: Chemistry; Computer science; Group (periodic table); Mathematics; Mutual aid; Physics; Political science; Pure mathematics; Transformation (genetics); Transformation group; dept.swk

Song of my Soul: A Memoir - Rakfeldt, Jaak (Mascot Books, 2025)
An Estonian saying holds that everyone has a unique song in their heart. This profound theme resonates throughout the pages of Song of my Soul. This work is not merely a memoir but a visceral journey through the heart of a besieged nation and a family’s unwavering struggle for survival. Rakfeldt’s narrative immerses the reader in the turbulent twentieth century, when Estonia became a pawn in Stalin and Hitler’s brutal power plays, marked by the devastating impact of three successive occupations. The author recounts his family’s harrowing escape to Sweden, their flight through Europe, and the process of building a new life in the West. He weaves together poignant episodes from his parents’ lives in Estonia, which were shattered by the Soviet invasion, forcing them to flee into forests and marshes and live as partisans hunted by Russian death squads. Beyond the historical account, Song of my Soul is a deeply personal journey. Rakfeldt begins to reclaim his ancestral heritage and fill the void left by displacement and loss. He grapples with questions of identity and belonging. This book serves as a testament to the resilience of refugee families and chronicles the suffering of the Baltic people. It resonates with anyone who has faced immigration challenges and with those seeking to understand the lasting strength of the human spirit.
Keywords: dept.swk

From the guest editor: what is a Festschrift? By Lorrie Greenhouse Gardella - Gardella, Lorrie (Social Work With Groups, 2025)
Keywords: Climate change; Greenhouse; Greenhouse effect; Greenhouse gas; Work (physics); dept.swk

Exploring Black Maternal Suicidal Ideation: A Pilot Study Exploring Risk and Protective Factors for Perinatal Suicidal Thoughts in Black Women - Welz, Natasha (Journal of Racial and Ethnic Health Disparities, 2025)
Keywords: Black women; Exploratory research; Feeling; Mental health; Occupational safety and health; Postpartum period; Pregnancy; Public health; Racism; Suicide prevention; dept.swk

“Not Just on the Sideline”: A Phenomenological Study of Disability, Belonging, and Exclusion - Gackenheimer, Christopher; Garrison, Brianna (Children & Schools, 2025)
Keywords: Identity (music); Inclusion (mineral); Inclusion–exclusion principle; Interpretative phenomenological analysis; Mainstream; Mainstreaming; Psychology of self; Qualitative research; Special education; adolescents; belonging; dept.swk; disability; inclusion; special education

Developing online considerations for the IASWG standards on Social Work with Groups: a tribute to Charles Garvin - Macgowan, Mark; Gardella, Lorrie; Simon, Shirley; Prinsloo, Reineth; van Baar, Huub; Seck, Mamadou; Astray, Andrés; Cañizares, Catalina; Muskat, Barbara (Social Work With Groups, 2025)
Keywords: Charles D. Garvin; Criminology; Engineering; Environmental ethics; IASWG standards for social work practice with groups; Law; Philosophy; Political science; Psychoanalysis; Psychology; Social work; Sociology; Tribute; Work (physics); dept.swk; group work; internationalization; online practice; social work with groups; translation; virtual practice

Self-Concept Among Formerly Incarcerated Sexual Minority Women - Stone, Al; Smoyer, Amy; D’Angelo, Karen (Social Sciences, 2025)
Sexual minority women (SMW) are a resilient yet vulnerable population who may experience poor psychosocial outcomes due to minority stress associated with their marginalized status and traumatic experiences resulting from interpersonal and structural violence. When SMW are incarcerated, the trauma of this experience can exacerbate existing mental health challenges. Self-concept is a key measure of mental health that is associated with increased self-efficacy and positive psychosocial outcomes. This analysis explores the ways in which incarceration impacts the self-concept of SMW. Secondary data analysis of three qualitative interviews with formerly incarcerated SMW was conducted. Specifically, Gilligan’s Listening Guide was used to create “I poems” that articulate the participants’ narratives and contrapuntal voices. These poems were then analyzed to build knowledge about participants’ self-concept. This analysis informs our understandings of self-concept among SMW, violence against women, the vulnerability of binary constructs, and the ways in which people negotiate past, present and future selves. The findings can inform interventions that seek to mitigate the psychosocial risks faced by SMW and formerly incarcerated people and improve outcomes for these populations.
Keywords: Clinical psychology; Developmental psychology; LGBT; Listening Guide; Psychology; Sexual minority; Sexual orientation; Social psychology; dept.swk; incarceration; lesbian; qualitative; self-concept; sexual minority women; transgender

Insomnia Symptoms, Mental Health Diagnosis, Mental Health Care Utilization, and Perceived Barriers in U.S. Males and Females - Sawadogo, Wendemi; Njoku, Anuli; Jegede, Joy (Journal of Clinical Medicine, 2025)
Objective: We aim to determine the association between insomnia symptoms and mental health in females and males and compare mental health care utilization and perceived barriers between females and males with insomnia symptoms. Methods: This is a cross-sectional study using the National Health Interview Survey. Insomnia symptoms included self-reported “trouble falling asleep”, ‘trouble staying asleep”, and “waking up feeling not well rested”. Mental health included self-reported anxiety and depression. Multivariable logistic regression was used to assess the association between insomnia symptoms and mental health in females and males. Results: A total of 26,691 adults were included. The mean age was 48.2 years; 51.4% were females, and 48.6% were males. Insomnia symptoms were associated with anxiety and depression for both females and males. These associations were stronger in younger adults (<50 years) than older adults (≥50 years). Females with insomnia symptoms were more likely to receive mental health care (OR = 1.7; 95% CI = 1.53, 1.87) but also to delay mental health care because of its cost (OR = 1.96; 95% CI: 1.67, 2.30) or needed mental health care but did not get it because of the cost (OR = 2.14; 95% CI: 1.82, 2.50) than their males counterpart. Conclusions: Insomnia symptoms were associated with mental health in females and males, being stronger in younger adults than older adults, with gender differences in mental health care utilization and financial barriers to mental health care. Holistic approaches involving prevention and better access to mental health care are warranted.
Keywords: Anxiety; Cross-sectional study; Depression (economics); Feeling; Health care; Insomnia; Internal medicine; Logistic regression; Medicine; Mental health; Psychiatry; Psychology; dept.pch; dept.swk; peer-reviewed

Perceived Religious Social Support in Faith Communities for Caregivers of Persons Living with Dementia - Garrison, Brianna; Myers, Dennis; Parrish, Danielle; Oxhandler, Holly (Journal of Gerontological Social Work, 2025)
Keywords: Dementia; Faith; Gerontology; Medicine; Psychology; Psychotherapist; Social support; caregiver; dept.swk; faith community; peer-reviewed; social determinants of health; social support